Isolation and Characterisation of Essential oils of Mango (M. indica) Leave - Abubakar, Auwal; Shagal, Mohammed Hassan; Milan, Charles (Biology, Medicine, & Natural Product Chemistry, 2024)
This research work aimed at isolation and characterisation of essential oils of Mangifera. indica (M. indica) leaves. Phytochemical screening was carried out to determine the bioactive components present in the leaf sample as well as the antimicrobial activity of the crude ethanolic extract. The percentage yield of essential oils (colourless) of the leaf was 0.19%. The phytochemical screening revealed the presence of alkaloid, glycoside, flavonoid, saponin and tannin.  Steroids was absent in the extract. The antimicrobial evaluation of the essential oil of M. indica leaf revealed a significant activity (zone of inhibition). The percentage (%) of Diphenyl picryl hydrazine (DPPH) scavenged of antioxidant activities for the essential oils of M. indica at different concentration of 5µl, 10µl, 25µl and 100 µl showed a significant antioxidant activity. In concluded results, it’s clearly observed that, when the concentration of both ethanolic extract and essential oils leaf sample increases, the antimicrobial and antioxidant properties increases when compared to the standard (Amoxicillin) and that of essential oils has a significant property than other extracts. Considering the results of phytochemical screening, it’s also a potential source of cost-effective food supplements, nutritive ingredients and antibacterial agent for improving human health and curing acute and chronic diseases. The GC-MS analysis of the essential oils for the leaf sample revealed fifty two (52) different chemical compounds which include Alloaromadendrene, Humulene, Bicyclo[4,4,0]dec-1-ene, 2-isopropyl-5-methyl-9-methylene, Bicyclo[7.2.0]undec-4-ene,4,11,11,-trimethyl 8-methylene-,[1R-(1R*,4Z,9S*)].